جهود التنمية والدعم الحكومي لصناعة المنتجات الزراعية في ليبيا 1951 – 1969م (دراسة تاريخية) - أبوسته عبد الحكيم الطاهر حسين (Al-Qurtas, 2026)
جهود التنمية والدعم الحكومي لصناعة المنتجات الزراعية في ليبيا 1951 – 1969م (دراسة تاريخية)